Death thoughts predict increased depression for those with low self-worth. Issue 4 (21st April 2022) - Fairlamb, Samuel; Juhl, Jacob
Abstract: Terror management theory specifies that a sense of self-worth is necessary to prevent the awareness of death from undermining psychological well-being. We tested the theory's claims about well-being within the context of depression, by measuring self-worth, death-thought accessibility, and depression in an online study ( N = 365). Consistent with the theory, death-thought accessibility predicted increased depression, but only among those with low, not high, self-worth. Our findings support existential clinical theorists' claims for psychological therapies to appreciate the underlying reasons for the need for self-worth.